Pattern of Common Paediatric Diseases at Spencer Eye Hospital - Arshad Shaikh, M.S Fahmi, M. Rais, Uzma Fasih, Atiya Rahman (Pakistan Journal of Ophthalmology, 2018)
Purpose: To determine the pattern of common paediatric ocular diseases presenting at outpatient department of Spencer Eye Hospital. Material and Methods: It was a hospital based descriptive cross sectional type of study carried out at OPD of Spencer Eye Hospital from March 2012 – May 2012 and included 370 patients. A detailed history was taken regarding the ocular disease and examination was carried out in detail on slit lamp, direct and indirect fundoscopy was done where required. Refraction was done and examination under anesthesia was done if required. Diagnosis was established and recorded. Patients were managed accordingly. Data analysis was done on SPSS programme version 14. Results: We studied 370 patients from March 2012 – May 2012. There were 220 (59.50%) male patients and 150 (40.5%) female patients. Most frequent presenting age group was 6 – 10 years (41.62%). Mean age of the patients was 8.24 ± 3.7 years. Bacterial conjunctivitis was most frequently found ocular disease (26.77%) followed by Trachoma (20%) while vernal catarrh was present in 9.73% patients. Refractive errors were present in 8.11% patients and ocular trauma in 6.76% patients. Congenital cataract presented in 5.68% of patients. Squint was found in 3.51% of patients. Presentation of corneal ulcer was in 2.70% patients. Congenital diseases were not much prevalent. Conclusion: Paediatric ocular disorders are of utmost importance. Their early diagnosis is greatly helpful in reduction of preventable childhood blindness. Electronic media should educate about the importance of paediatric ocular disorders.